A Proposal for a Dowry Prohibition Law in Sri Lanka: An Assessment in the Light of Indian Dowry Prohibition Act No. 28 of 1961 - Pathirana, M.P.S. K. (My University, 2012)
Most of the countries including South Asian countries have started to include specific measures into their domestic laws to protect women’s rights in order to comply with international standards. Nonetheless, the tragic situation is that when implementing these laws, the objectives to promote and protect human rights of women are diminished or negated by the impact of some extraneous factors. Those factors are rooted in social, cultural, religious, political and some of other patriarchal social values. ‘Dowry’ is the one of the critical areas which contradicts international standards, but still prevails with the support of above mentioned extraneous factors. The matter of dowry is yet to be addressed by the legislature or the judiciary in Sri Lanka. This paper aims to propose a new policy to prohibit dowry in Sri Lanka in the light of Indian Dowry Prohibition Act of 1961(hereinafter mentioned as ‘IDPA’). The Sri Lankan context indicates that dowry has over time transformed into a marriage gift to the bridegroom in all communities. Dowry still prevails in the Sinhala and Tamil communities as a customary requirement and as a legal requirement in the Muslim community under the Islamic religious law in Sri Lanka. Dowry has both social and legal legitimacy in Sri Lanka and most of the times it is openly referred to in marriage advertisements in public newspapers in Sri Lanka. However, this practice of dowry in its manifestation undervalues women and commercializes the marriage relationship. Nonpayment of dowry has result in harassment, violence against women, breakdown of spousal relationships and conflict with extended family. In addition, Sri Lankan judiciary has also not taken an effort to consider the matter of the legality or illegality of giving and taking dowry.1 The dowry problem in India arose out of a complex social situation and it was further strengthened by tradition, myths, and religion. Nevertheless, the most problematic situation in India regarding dowry was that it led to a lot of dowry deaths and bride burning by the groom or his relations. In this scenario, the IDPA had come in to force to protect the rights of women in India in relation to the matter of dowry. The purpose of IDPA is to prohibit the giving and taking of dowry with a view to prevent dowry deaths.2 Although there are some problems relating to its implementation, the IDPA is a remarkable achievement of the legal system of India. As this legislation is enforced in multiple community which bears a gamut of personal laws and religious customs which contradict with the international standards.